Assessing alimony rights violations: a neutrosophic multi-criteria evaluation - Vanessa Lisseth Montenegro Altamirano; Jaime Rodrigo Cadena Morillo; Carmen Marina Méndez Cabrita (Journal of Fuzzy Extension and Applications)
This study addressed the violations of child support rights in the province of Pichincha, employing a Multi-Criteria Decision-Making (MCDM) methodology based on the TODIM and PROMETHEE methods in conjunction with neutrosophic theory. The research aimed to identify critical failures in the child support administration system within the study area. The investigation focused on the complexity of the violations, which require decision-making that considers multiple interrelated criteria. Five key violations were identified, including non-compliance with payment obligations and unilateral modification of agreements, which negatively affect the beneficiaries' well-being. Four main evaluation criteria were selected and assessed with the help of five experts. The applied methodology combined the TODIM and PROMETHEE multi-criteria methods to rank the violations according to their impact, utilizing neutrosophic theory to handle the uncertainty inherent in decision-making within this context. The results indicated that unilateral modification of agreements was the most critical violation, with significant effects on the beneficiaries' economic stability. The lack of access to financial information was also highlighted as a relevant issue. The combined use of these methods allowed for a more accurate evaluation of the violations, providing new approaches to improve the administration and protection of child support rights.